Structure and mechanical properties of Zn-1Cu-1Mn and Zn-0.8Al-0.5Ag alloys processed by ECAP - Abdrakhmanova, E. D.; Nugamanov, F. V.; Khafizova, E. D.; Islamgaliev, R. K.; Polenok, M. V.; Nafikov, R. K.; Yilmazer, H. (SPRINGER, 2024)
In this work, Zn-1Cu-1Mn and Zn-0.8Al-0.5Ag alloys are considered as alternative materials for producing ureteral stents. To improve the mechanical properties, these alloys were deformed by equal-channel angular pressing (ECAP). The microstructure, microhardness and strength are investigated after tensile tests. The effects of grain refinement and twinning on mechanical properties have been investigated and discussed. It has been established that the presence of twins in the initial microstructure of the alloys leads to the brittleness of the material, which can be eliminated through deformation processing. An increase in the volume fraction of the MnZn13 phase has been observed in the Zn-1Cu-1Mn alloy, as well as a precipitation of the Ag3Al and AgZn3 phases in the Zn-0.8Al-0.5Ag alloy.
Keywords: Zinc alloys; Biodegradable implants; ECAP; Microstructure; Mechanical properties; 691.75; BEHAVIOR; Physics